Effects of triazolodiazepine on the production of interleukin-6 from murine spleen cells and rabbit synovial cells in vitro - Dian-Wen Ju; Qin-Yue Zheng; Xue-Tao Cao; Qing-Hua Zheng; Xiao-Jun Guan; Hong-Bin Wang (Mediators of Inflammation)
Interleukin-6 (IL-6) is a multifunctional cytokine that regulates the immune response, acute phase anaphylactic reaction, and haematopoiesis. Lipopolysaccharide (6–24 μg/ml) significantly induced IL-6 release from murine spleen cells. In cultured rabbit synovial cells interleukin-1 (IL-1, 1–10 U/ml) induced IL-6 production in a concentration-dependent manner. Triazolodiazepine (Tri) is a hetrazepine platelet-activating factor antagonist. In this study we found that Tri (0.1–10 μmol/l) exerted strong inhibitory effects on LPS stimulated IL-6 production in murine spleen cells. Kinetic studies showed that the inhibition of IL-6 release was time-independent. In rabbit synovial cells Tri also reduced IL-6 release induced by IL-1 and tumour necrosis factor. Inhibition of cytokine production by Tri may partially explain its wide and strong anti-inflammatory effects.